Association of adolescent self-esteem in 2014 and cognitive performance in 2014, 2016, and 2018: a longitudinal study - Wang, Xue; Liu, Yu; Zhao, Zhe; Liu, Wenting; Chen, Yuqi; Chen, Yu; Zang, Shuang (Frontiers in Psychology, 2023)
Background: Cognition has long been regarded as a significant factor influencing individuals’ lives. Prior studies have underscored that self-esteem is associated with cognition, and there exists a knowledge gap regarding whether self-esteem remains associated with subsequent cognitive performance during adolescence, a crucial period for neurological development and influencing adult outcomes. Methods: We conducted this population-based study using longitudinal data stretching three waves (2014, 2016, and 2018) of surveys from the nationally representative China Family Panel Studies (CFPS) to explore the association between adolescents’ self-esteem in 2014 and cognitive performance in 2014, 2016, and 2018. Results: The results of the present study showed that self-esteem during adolescence in 2014 was significantly associated with cognitive performance in 2014, 2016, and 2018. This association remained robust after an extensive range of covariate adjustments (e.g., adolescents, parental, and family characteristics). Conclusion: The findings in this study provide further insight into the understanding of the related factors for cognitive development across the life course and highlight the importance of improving individual self-esteem during adolescence.